Mechanical properties of hybrid fibres reinforced polymer modified mortar in promoting sustainable materials in construction / Azamuddin Husin, Mahyuddin Ramli and Cheah Chee Ban - Azamuddin, Husin; Mahyuddin, Ramli; Cheah, Chee Ban (Universiti Teknologi MARA, Perak, 2019)
Fibre reinforced polymer modified mortar (PMM) was widely accepted for multipurpose application in construction industry. However the use of natural fibre in cementitious material in terms of durability performance was not encouraging. This paper aims to investigate the mechanical properties of the hybrid fibre namely kenaf, polypropylene and bar chip in polymer modified mortar with a low water-cement ratio. The results concluded that the hybridisation of 0.4% kenaf, 0.6% polypropylene and 0.6% bar chip (G sample) exhibited the significant increment of compressive and flexural strength for both curing regimes.